STUDY ON THE PHYSIOLOGY OF ENVIRONMENT POLLUTION AND THE EFFECT OF HEATING ON THE MALATHION RESIDUE ANALYZED USING RADIOTRACER METHOD - Hamzah, Razak Achmad (Makara Journal of Science, 2011)
The aim of this study is to determine, the comparison of absorption by aquatic plants Hydrilla verticillata and Water hyacinth (Eichhomia crassipes) of malathion insecticide residues in water and comparison of malathion concentration in tissues of fish fed with of contaminated water plants (Water hyacinth) with tissues of fish, which was not fed contaminated water plant. The effect of heating the contaminated fish tissue, on its level in tissues of rats that consume it. For the first experiment (aquarium filled with 3 litre of water + H. verticillata 100 gr + Water hyacinth 100 gr + 20 uci 14C-labeled malathion); for the second experiment (the first aquarium filled with 3 litre of water + 30 tails of goldfish + 20 uci 14C-labeled malathion; second aquarium filled with 3 litre of water + Water hyacinth 100 gr + 30 tail of goldfist + 20 uci 14C –labeled malathion. For the third experiment (most of contaminated fish tissue in the second experiment was dried at room temperature and then given to 30 mice and partly heated and then given to another 30 mice). Malathion levels were then analyzed by using a liquid scintillation counter LSC-753 (Aloka). The results of all treatments were compared using the Student t-test. It can be concluded, H. verticillata was more efficient compared to the enceng gondok in absorbing the insecticide malathion residues in water; malathion concentration in the tissues of fish fed Water hyacinth was higher than those of fish not fed Water hyacinth; contaminated fish tissue residues of malathion, although be heated, can not be lowered significantly, levels in the tissue.